If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(y + -3y) + 3 = -3(3y + -1y) + 6 + 11y Combine like terms: y + -3y = -2y -3(-2y) + 3 = -3(3y + -1y) + 6 + 11y Remove parenthesis around (-2y) -3 * -2y + 3 = -3(3y + -1y) + 6 + 11y Multiply -3 * -2 6y + 3 = -3(3y + -1y) + 6 + 11y Reorder the terms: 3 + 6y = -3(3y + -1y) + 6 + 11y Combine like terms: 3y + -1y = 2y 3 + 6y = -3(2y) + 6 + 11y Remove parenthesis around (2y) 3 + 6y = -3 * 2y + 6 + 11y Multiply -3 * 2 3 + 6y = -6y + 6 + 11y Reorder the terms: 3 + 6y = 6 + -6y + 11y Combine like terms: -6y + 11y = 5y 3 + 6y = 6 + 5y Solving 3 + 6y = 6 + 5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5y' to each side of the equation. 3 + 6y + -5y = 6 + 5y + -5y Combine like terms: 6y + -5y = 1y 3 + 1y = 6 + 5y + -5y Combine like terms: 5y + -5y = 0 3 + 1y = 6 + 0 3 + 1y = 6 Add '-3' to each side of the equation. 3 + -3 + 1y = 6 + -3 Combine like terms: 3 + -3 = 0 0 + 1y = 6 + -3 1y = 6 + -3 Combine like terms: 6 + -3 = 3 1y = 3 Divide each side by '1'. y = 3 Simplifying y = 3
| 8m-4=5m+5 | | 4m+33=77m | | X=9+3(14+4x) | | 3(8y-6)=6y | | n+6=-4 | | -2(8-3y)=7y+2y | | 4m-6=16m | | 0.3x-0.1(3-x)=2.3 | | 0.6x-2.9=4.8x+1.8 | | 32=4(y+6) | | 2(x-8)=26 | | 2x+6-2x=38 | | (9x+7)-(x+3)= | | 107=x-98 | | 6x^5=6x^3 | | -8(2w-6)+4(-1-5w)=0 | | 4(5x^2+2)=44x | | 3y+4y+7=-63 | | 4(a-8)+12=2(a-7) | | x^4-x^3-2x^2-4x-8=0 | | B=zm+z | | 4(2x-5)=8x-7 | | x*x-3x-8=0 | | 0.02x+0.35=1.25 | | 0.5x+8=-9 | | 0.3y+0.9=0.4-0.2y | | 12x+10y=-5 | | (2x-5+x)=38 | | -5x=-36+4x | | 2(9+x+6)=52 | | 7(x+3)=63 | | 6.4y=-2 |